Penerapan Intervensi Fisioterapy Dada Dengan Masalah Bersihan Jalan Nafas Yang Tidak Efektif Pada Anak Dengan Bronchopneumonia - Din, Yasinta Emilia; Maria Astrid (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The application of chest physiotherapy in children with bronchopneumonia can help overcome the problem of ineffective airway hygiene. Bronchopneumonia is an infection of the lungs that causes phlegm, which can interfere with the breathing process and cause difficulty breathing. This study aims to apply the application of chest physiotherapy in improving airway hygiene in children with bronchopneumonia at Hospital X, South Tangerang City. The method used in this study is a descriptive case study with a qualitative approach. Chest physiotherapy interventions, including postural drainage, chest percussion, and vibration, were carried out for three consecutive days. The results showed a significant increase in the patient's airway hygiene, which was indicated by reduced coughing, increased oxygen saturation, and easier phlegm expectoration. This therapy also helps improve breathing patterns and reduce symptoms of bronchopneumonia. It is estimated that the application of chest physiotherapy can be an effective choice in the treatment of children with bronchopneumonia.